Impact of tocilizumab on clinical outcomes in severe COVID-19 patients and risk of secondary infection: A case-control study - ERTÜRK ŞENGEL, BUKET; ILGIN, CAN; TİGEN, ELİF; GÜL, FETHİ; KABADAYI, FEYYAZ; CİNEL, İSMAİL HAKKI; KORTEN, VOLKAN; SİLİ, ULUHAN; ODABAŞI, ZEKAVER (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: This study aimed to identify the effect of tocilizumab (TCZ) on clinical outcomes in severe COVID-19 patients. Material and Methods: We included hospitalized COVID-19 patients with an initial WHO scale >= 4. We matched the patients with baseline characteristics by using propensity scores. Then, we selected patients with C-reactive protein levels above 30 and showing an upward trend. We assessed the effect of TCZ in patients on clinical outcomes by using Mann - Whitney U and Chi-square tests. Results: Of 200 patients who had an initial WHO scale >= 4, 42 (21%) were given it? in addition to standard of care (SOC). Twenty-five patients (50%) needed mechanical ventilation (MV) in the TCZ group, compared with 35 (21%) of 158 patients with SOC (p<0.01). Nineteen (45%) and 37 (23%) patients died in 30 days in these groups, respectively (p <0.01). The secondary infection rate was significantly higher in the TCZ group (p=0.004). However, no difference was observed in all these parameters in the propensity score-matched cohort (14 patients in ICZ and 14 in the SOC group) (p=0.45, 0.45, 1.0 respectively). Conclusions: Tocilizumab does not provide a beneficial effect on MV requirement and mortality in severe COVID-19, and it does not increase the risk of secondary bacterial infection.
Keywords: COVID-19; IL-6; SARS-CoV-2; Tocilizumab; RHEUMATOID-ARTHRITIS; EFFICACY